Maxwell Weber: capstone - Weber, Maxwell, artist (Colorado State University. Libraries, 2022)
The artist's statement: In my photographic practice, I primarily focus on the human-altered aspects of the western American landscape. Documenting the results, byproducts and repercussions of the United States manifesting its destiny across the west. I find the built environments to be reflective of the cultures that create them. I am also interested in the economic and political aspects of the environments and subjects that I photograph. Specifically I am focusing on a current trend in architecture which began with "five over one" apartment buildings. They are typically multifamily housing units with sleek and repetitious exteriors, and often leave the ground floor as commercial space. This trend is largely driven by economics as these buildings are very cost effective to construct. The buildings can be luxury, low-income, or student housing, but there is no way to tell which it is from the outside. I photograph these buildings with a 4x5 field camera using the wet plate collodion process. The wet plate collodion process, sometimes known as tintype, is a 19th century photographic process which predates the silver-gelatin process, the basis of modern film. In the modern version of this process, a glass or aluminum plate is coated with collodion, which becomes the substrate that holds the image. When the coated plate is submerged in a silver nitrate bath, it becomes sensitive to light and an image can be made on it. The plate is only sensitive to light while it is wet and therefore must be developed before it dries. I use this historic and slightly dangerous method of making photographs both because of the way the resulting images look and to be fully connected to the photographic process. While digital manipulations can evoke or mimic wet plate, nothing looks like a wet plate photograph. I am using the wet plate collodion process to contrast 21st century architectural trends with 19th century photographic technology. I find “five over one” buildings to be stylistically, spiritually and physically hollow. Conversely, I find wet plate collodion images to be stylistically, spiritually and physically rich. It is interesting looking at soulless buildings through the filter of a very soulful process. The bland repetition of the architectural forms are echoed and contrasted by the unique mark making of wet plate.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: photography